Down-regulation of miR-452 is associated with poor prognosis in the non-small-cell lung cancer - He, Zhicheng; Xia, Yang; Liu, Bin; Qi, Xiaotong; Li, Zhi; Wang, Jun; Chen, Liang; Chen, Yijiang (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: Non-small cell lung cancer (NSCLC) remains the most life-threatening cancer in the world. The aim of the current study was to investigate the value of miR-452 for the prognosis of patients with NSCLC. Methods: Real-time quantitative PCR (qRT-PCR) was used to test the expression level of miR-452 in 161 paired clinical NSCLC tissues and their adjacent tissues. Survival curves were made and the log rank test was used to analyze the survival difference between both groups with higher and lower expression level of miR-452. Univariate and multivariate Cox regression analyses were finally used to determine the independent factors for overall survival (OS) and disease-free survival (DFS) times. Results: The miR-452 expressions in tumor samples (n=161) were comparably lower than those in the adjacent tissues. miR-452 expression levels were significantly associated with tumor differentiation grade, tumor size and lymph nodes metastasis. Furthermore, Kaplan-Meier survival curves showed that patients with higher expression of miR-452 was confirmed to have more favorable OS (P=0.004) and DFS (P=0.026). Multivariate survival analysis verified that miR-452 expression level, as well as lymph nodes metastasis, was an independent predictor of both OS and DFS for NSCLC patients. Conclusions: Our study demonstrated that miR-452 functioned as a novel diagnostic biomarker and a promising prognostic predictor for NSCLC patients.